Effects of Three Typical Resistivity Models on Pulsed Inductive Plasma Acceleration Modeling - 孙新锋;贾艳辉;张天平;吴宸辰;温晓东;郭宁;金海;柯于俊;郭伟龙 (Chinese physics letters, 2017)
The effects of three different typical resistivity models（Spitzer, Z＆L and M＆G） on the performance of pulsed inductive acceleration plasma are studied. Numerical results show that their influences decrease with the increase of the plasma temperature. The significant discriminations among them appear at the plasma temperature lower than 2.5 eV, and the maximum gap of the pulsed inductive plasma accelerated efficiency is approximately 2.5%.Moreover, the pulsed inductive plasma accelerated efficiency is absolutely related to the dynamic impedance parameters, such as voltage, inductance, capacitance and flow rate. However, the distribution of the efficiency as a function of plasma temperature with three resistivity models has nothing to do with the dynamic impedance parameter.